PENINGKATAN ASPEK PERENCANAAN UNTUK MEWUJUDKAN SEKOLAH EFEKTIF DALAM LEMBAGA PENDIDIKAN ISLAM - Sumarto Sumarto (Universitas Muhammadiyah Metro, 2019)
The future of schools is largely determined by managerial factors one aspect is planning. Small schools will develop significantly when professionally managed. With the same easy management, large schools will grow. Conversely, advanced schools will experience a setback when management is not well managed. If schools neglect management, small schools will close down in the face of multimensional dimensions. Planning patterns in schools that have not been conducive to face the challenges of modernization even need to be changed into planning patterns that are more responsive to the needs of society and the demands of the times. The pattern must lead to activities that involve more and more people in the leadership ranks, to jointly run the wheels of the school organization towards conditions that are advanced and established, both in terms of institutional, educational system, learning process, and quality of students so that they can realize effective school.Keywords: Planning, Effective Schools and Islamic Education Institutions